Effect of Cell Culture Medium on the Proliferation and Stemness of CD24-/CD44+ Human Breast Cancer Stem Cells - Yalista Fatia Nadia; Resda Akhra Syahrani; Sekar Arumsari; Mohamad Sadikin; Septelia Inawati Wanandi (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Cancer stem cells (CSCs) is defined as tumor initiating cells within tumor that maintain stemness properties and tumorigenicity. Extracellular pH of CSCs in in vitro condition is important for supporting cell proliferation which may also regulate the expression of stemness markers such as OCT4. This work aimed to examine the effect of cell culture media on the proliferation and stemness of human breast cancer stem cells (BCSCs).METHODS: Human CD24-/CD44+ BCSCs were grown in Dulbecco's Modified Eagle Medium/F-12 (DMEM/F-12) with 15mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), without HEPES and adjusted to pH 7.4, or without HEPES but pH was not adjusted. BCSCs were grown under standard conditions for various days. Viable cell number was measured using trypan blue exclusion, whereas proliferation rate using MTS assay. OCT4 mRNA and protein were analyzed using quantitative real time PCR (qRT-PCR) and Western Blot assay, respectively. In vitro tumorigenic activity was determined using mammosphere formation unit (MFU) assay.RESULTS: Our results showed a higher viable cell number and proliferation of BCSCs in DMEM/F-12 HEPES (-) compared to HEPES (+) medium until 4 day incubation. OCT4 mRNA and protein level, as well as MFU of BCSCs were significantly higher in HEPES (-) compared to HEPES (+) medium on day 2.CONCLUSION: DMEM/F-12 medium without HEPES facilitates CD24-/CD44+ BCSCs to have higher proliferation and stemness on day 2 incubation compared to those with HEPES.KEYWORDS: breast cancer, cancer stem cell, OCT4, stemness, proliferation